Creativity and Conventionality in Heritage Speaker Bilingualism. (13th May 2019) - Zyzik, Eve
Abstract: This article examines the performance of heritage speakers on a bimodal acceptability judgment task that targeted morphologically complex words. A major goal of the study was to compare participants' acceptance of conventional and creative words. Data were collected from 57 adult heritage speakers of Spanish who were subsequently divided into two groups based on language dominance; 18 monolingual native speakers served as a control group. The data were analyzed with a mixed‐effects logistic regression model, which showed that item type (conventional vs. creative) had a very strong effect on participants' performance. In addition, there were differences between Spanish‐dominant and English‐dominant heritage speakers, but only on the creative items. The results are discussed in relation to the Principle of Contrast (Clark, 1987) proposed for first language acquisition and the role of analogy in making acceptability judgments. Abstract :